2009
DOI: 10.1021/ja907792d
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Induced Photodegradation of Toxic Pollutants with Ag−AgI/Al2O3 under Visible-Light Irradiation

Abstract: A plasmonic photocatalyst Ag-AgI supported on mesoporous alumina (Ag-AgI/Al(2)O(3)) was prepared by deposition-precipitation and photoreduction methods. The catalyst showed high and stable photocatalytic activity for the degradation and mineralization of toxic persistent organic pollutants, as demonstrated with 2-chlorophenol (2-CP), 2,4-dichlorophenol (2,4-DCP), and trichlorophenol (TCP) under visible light or simulated solar light irradiation. On the basis of electron spin resonance, cyclic voltammetry analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
276
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 544 publications
(285 citation statements)
references
References 38 publications
6
276
2
1
Order By: Relevance
“…1). The rate of photocatalytic degradation of EE2 exhibited a slight variation in the presence of NaHCO 3 , but a contrast test indicated that this was due to an increase of pH [22], implying that h + have negligible contribution on the degradation of EE2. p-benzoquinone quencher had almost no influence on the photocatalytic degradation of EE2, indicating no ·O 2 -existed in the solution.…”
Section: Photocatalytic Mechanism Of Ag/agcl @ Chiral Tio 2 Nanofibersmentioning
confidence: 92%
“…1). The rate of photocatalytic degradation of EE2 exhibited a slight variation in the presence of NaHCO 3 , but a contrast test indicated that this was due to an increase of pH [22], implying that h + have negligible contribution on the degradation of EE2. p-benzoquinone quencher had almost no influence on the photocatalytic degradation of EE2, indicating no ·O 2 -existed in the solution.…”
Section: Photocatalytic Mechanism Of Ag/agcl @ Chiral Tio 2 Nanofibersmentioning
confidence: 92%
“…It has been reported that the Ag/AgI@Al 2 O 3 -supported plasmon-induced photocatalyst possesses much higher photocatalytic stability and activity than those of the bare Ag/AgI photocatalyst for the decomposition and mineralization of the toxic organics. 14 Another recent work report also indicated that a nanocomposites made of Ag/AgX loaded graphene oxide (GO) (Ag/AgX@GO) has significantly enhanced photocatalytic activity and stability as compared to those of bare Ag/AgX (X = Cl, Br) plasmonic photocatalysts. 16 These research findings imply that the photocatalytic activity as well as the stability of Ag/AgX can be significantly enhanced by loading onto a suitable supporting material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11). Under visible irradiation, the photocurrent increased and then decreased to a stable value, resulting in a peak at 0.21 V on Ag-AgBr/Al 2 O 3 , which was assigned to the oxidation of Ag NPs due to the plasmon-induced charge separation [14,18,27]. The peak with weaker intensity was also observed on Cu 2 O-Ag-AgBr/Al 2 O 3 photoanodes, indicating the lower amount Ag NPs were photocorrosioned in the presence of Cu 2 O.…”
Section: Photostability and Agmentioning
confidence: 99%
“…In particularly, nanoparticles (NPs) of noble metals can strongly absorb visible light because of surface plasmon resonance, which greatly enhances the overall photocatalytic efficiency at the interface between the metal and the semiconductor [5][6][7][8][9][10][11]. Many plasmonic photocatalysts have been developed based on this phenomenon using a combination of Ag or Au NPs and semiconductor [3,[11][12][13][14][15]. The electron transfer was based on both photoexcitation of semiconductor and plasmon-excitations of noble metal NPs on the surface [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation